Absent Father Timing and its Impact on Adolescent and Adult Criminal Behavior - TenEyck, Michael F. (American journal of criminal justice, 2023)
Although prior research has examined the link between having an absent biological father and self-reported delinquency, few studies have assessed the influence of the timing of paternal absence (i.e., the child’s age when father leaves) on delinquency and adult criminal behavior. Using data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), the present study examines this relationship to determine whether the timing of biological father absence impacts delinquency, adult criminal behavior, and arrest across the life course. Results reveal that biological father absence before birth was related to criminal behavior in later adulthood. Having an absent father in early childhood (birth to age 5) was related to criminal behavior in early adulthood as well as arrest. An absent biological father in late adolescence (age 14 to 18) was associated with arrest. These findings suggest that: 1) the timing of father’s absence does not have a clear pattern of impact on delinquency and arrest and 2) the negative impact of having an absent biological father—at any time—may not appear until adulthood.